Intermittent exercise alters the heart rate-blood lactate relationship used for calculating the training impulse (TRIMP) in team sport players - Akubat, I.; Abt, G. (Journal of Science and Medicine in Sport, 2011)
Objectives: The training impulse (TRIMP) quantifies training dose by weighting heart rate according to the relationship between fractional elevation in heart rate ([Delta]HR) and blood lactate concentration (BLa). This study compared the physiological responses to intermittent and continuous exercise and their influence on TRIMP weightings. Design: Repeated measures crossover. Method: Twelve team sport players undertook a vVO2max test and then a continuous trial (CT) and intermittent trial (IT) in a randomised order. Each trial consisted of 4×4min stages corresponding to 25%, 50%, 75% and 100% of vVO2max. Trials were matched for distance and mean speed. Results: A repeated measures ANOVA revealed higher BLa for IT at 75% vVO2max (p=0.023) and 100% vVO2max (p=0.012); higher VO2 for IT at 25% vVO2max (p<0.001); higher [Delta]HR for IT at 25% vVO2max (p<0.001), 75% vVO2max (p=0.03) and 100% vVO2max (p=0.018); higher TRIMP weightings for IT at 0.9 [Delta]HR (p=0.018) and 1.0 [Delta]HR (p=0.005). Conclusions: Intermittent exercise alters the [Delta]HR-BLa relationship and TRIMP weightings at high exercise intensities. Determination of the training impulse from the [Delta]HR-BLa relationship derived from a continuous exercise protocol may underestimate the exercise [`]dose' of training and/or matches in team sport players.